Efektivitas Konsumsi Protein Hewani (Telur dan Ikan Lele) sebagai Strategi Penuntasan Stunting - Paramitha, Intan Azkia; Avianti Rahayu , Nova; Lufar, Nay; Arifiana, Ratna; Rosidi, Ahyar (Jurnal MID-Z (MIDWIFERI ZIGOT), 2025)
Based on the 2022 Indonesian Nutrition Status Survey (SSGI), the national prevalence of stunting was 21.6% and Central Java was 20.8%, with the highest prevalence in Central Java and the highest prevalence of stunting in young children in Pekalongan Regency at 23.1%. Growth retardation is a condition where the height or length of a baby's body becomes shorter than their age. Providing additional food to vulnerable groups is a complementary strategy to overcome nutritional challenges. Providing additional nutrition to babies is one effort to meet the nutritional needs of babies so that they can achieve optimal growth and development. This study is a quantitative study with a cross-sectional design that aims to determine the effectiveness of animal protein intake (eggs and fish) on stunted babies. The study was conducted in August by providing food in the form of cooked egg protein and fish to 30 respondents for 30 days. Univariate analysis used frequency distribution, and bivariate analysis used chi-square. The results showed improved nutritional status and decreased stunting before and after the intervention. The statistical test produced a p-value of 0.039, which shows that animal protein (eggs and fish) has an effect on stunting.